Insight into the Jet Emission Properties from Long-Term Monitoring of the TeV Blazar PG 1553+113 - Prandini, E.; Hovatta, T.; Stamerra, A.; Silvestri, G.; MAGIC collaboration (Italy, 2026)
PG 1553+113 is a distant TeV blazar known for its ~2.2-year periodic gamma-ray signal detected with Fermi-LAT. We present results from a decade-long, multiwavelength monitoring campaign of this source.
Our analysis confirms the periodicity in gamma-ray and optical bands; however, no significant periodicity is found at TeV and X-ray energies, based on observations with MAGIC and Swift-XRT, respectively. These findings, combined with a study of variability on different timescales, support a multi-zone emission scenario, as further corroborated by recent IXPE observations.
We test a two-zone, synchrotron self-Compton model on 2019 multi-frequency flare data. The long- and short-term variability, along with inter-band correlations from the monitoring, serve as key inputs to constrain the model, reducing the large degrees of freedom. Based on this approach, we propose a set of parameters that effectively describe the PG 1553+113 emitting region responsible for the observed radiation.
Proceedings of 39th International Cosmic Ray Conference (ICRC2025)